Smelting method of aluminum-free high-temperature alloy
By using the combination method of three-time composite deoxysulfur agent and nickel-magnesium alloy during the smelting process of aluminum-free high-temperature alloy, the problem of high oxygen, nitrogen and sulfur content during vacuum induction smelting is solved, and the purity of the alloy is significantly improved and performance.
Patent Information
- Application Number
- CN202411280471.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2025-02-11
AI Technical Summary
During vacuum induction smelting, the content of oxygen, nitrogen and sulfur in the aluminum-free high-temperature alloy is relatively high, resulting in a decrease in purity and affecting the overall quality of the alloy.
Using the addition of three-time composite deoxysulfur agent, the content of oxygen, nitrogen and sulfur in the melt of high-temperature alloy is gradually reduced through the principles of precipitation, deoxygenation and diffusion deoxygenation, and oxides and sulfides are formed through the magnesium element in the nickel-magnesium alloy. Further help remove harmful elements.
Through multiple refining, melt conditioning and high-temperature purification, the content of oxygen, nitrogen and sulfur in the high-temperature alloy melt is significantly reduced, and the purity and performance of the alloy are improved.
Smart Images

Figure BDA0005041476750000061 
Figure BDA0005041476750000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of alloy materials, and in particular to a smelting method of aluminum-free high-temperature alloys. Background Art
[0002] During vacuum induction melting, the carbon in the alloy combines with the oxygen in the raw materials to form carbon monoxide, which is removed by the vacuum system to achieve deoxidation. After that, aluminum is added to combine with the residual oxygen in the melt to form a complex structure of oxides, forming slag to precipitate deoxidation, further reducing the oxygen content in the melt. On the other hand, during vacuum induction melting, the gas deoxidation process is actually accompanied by denitrification, reducing the nitrogen content in the melt. Sulfur is a surface-active element, and reducing the oxygen and nitrogen content in the alloy melt is conducive to promoting the removal of sulfur in the melt.
[0003] However, for aluminum-free high-temperature alloys, due to the limitation of alloy composition, aluminum-based deoxidizers cannot be added during vacuum induction melting, and precipitation deoxidation cannot be performed. At this time, the contents of oxygen, nitrogen and sulfur are high, and the slag content is high, the purity is reduced, and the overall quality of the alloy is affected, so it needs to be improved. Summary of the invention
[0004] In order to improve the purity of aluminum-free high-temperature alloys, the present application provides a smelting method of aluminum-free high-temperature alloys.
[0005] The present application provides a smelting method for aluminum-free high-temperature alloys using the following technical solutions: A method for smelting an aluminum-free high-temperature alloy comprises the following steps: (1) placing a nickel plate at the bottom of a crucible, adding a composite deoxidizing sulfur agent A, and then placing nickel, molybdenum, tantalum, cobalt, chromium and iron at the bottom of the crucible in order, vacuuming and melting the materials, raising the temperature after the materials are melted, and adding a composite deoxidizing sulfur agent B for refining; (2) After refining, the temperature is lowered until the alloy liquid surface solidifies, and niobium, titanium and zirconium are added in sequence. Electric heating is applied until the added materials are completely melted, and then the melt is stirred for tempering treatment; (3) Adding composite deoxidizing sulfur agent C to the tempered melt for secondary refining, cooling the alloy liquid to form a film on the surface, adding nickel-magnesium alloy until it is completely melted, heating the alloy liquid, blowing argon gas from the bottom of the crucible, cooling the alloy liquid and then keeping the temperature, completing the high-temperature purification treatment, and performing continuous casting with electricity to complete the alloy smelting to obtain an aluminum-free high-temperature alloy.
[0006] By adding three composite deoxidizing sulfur agents, the contents of oxygen, nitrogen and sulfur in the high-temperature alloy melt are gradually reduced. The three composite deoxidizing sulfur agents work together through the principles of precipitation deoxidation and diffusion deoxidation to help remove oxygen in the high-temperature alloy through gas and slag, and nitrogen and sulfur simultaneously form nitrides and sulfides and are discharged from the system; the magnesium element in the nickel-magnesium alloy further helps the removal of harmful elements by forming oxides and sulfides, while improving the properties of the slag, promoting slag agglomeration and floating, and improving the purity of the high-temperature alloy; through two refining, melt tempering treatment and high-temperature purification treatment, the oxygen, nitrogen and sulfur in the high-temperature alloy melt are removed, the content of harmful impurities is reduced, the segregation of alloy elements is reduced, and the performance of the high-temperature alloy is improved.
[0007] Preferably, the aluminum-free high-temperature alloy comprises the following components in fractions by mass: 35-45% nickel, 2.3-2.7% tantalum, 1.6-2.4% molybdenum, 8-10% cobalt, 10-12% chromium, 2.5-3.2% niobium, 0.8-1.2% titanium, 0.05-0.1% zirconium, and the remainder is iron and unavoidable impurities.
[0008] Preferably, the composite deoxidizing sulfur agent A comprises silicon-manganese alloy and carbon.
[0009] Silicon manganese alloy can effectively remove oxygen and sulfur elements by forming silicon dioxide, manganese oxide, silicon sulfide and manganese sulfide to form slag in the molten steel for removal; carbon combines with oxygen elements in the melt during the smelting process, and carbon monoxide is removed through a vacuum system to achieve deoxidation; harmful elements in the melt are preliminarily removed through the composite deoxidizing sulfur agent A.
[0010] Preferably, the amount of the composite deoxidizing sulfur agent A is 0.5-1% of the total mass of the aluminum-free high-temperature alloy.
[0011] Preferably, the composite deoxidizing sulfur agent B comprises calcium silicon cored wire and carbon, and the calcium silicon cored wire comprises a steel sheet and a core powder layer.
[0012] Silicon-calcium cored wire can effectively penetrate into the molten steel, reduce the impact of rapid evaporation of calcium on the deoxidation and desulfurization performance, and improve the removal effect of harmful elements. At the same time, calcium helps to remove silicon oxides and sulfides, reducing the impact of inclusions on the performance of high-temperature alloys.
[0013] Preferably, the core powder layer comprises 27-31% silicon, 15-17% cerium, and the remainder is calcium.
[0014] Cerium can further promote the removal of oxygen, effectively confine oxygen, and at the same time form a stable sulfide slag, thereby improving the effects of deoxidation and desulfurization.
[0015] Preferably, the amount of the composite deoxidizing sulfur agent B is 0.05-0.1% of the total mass of the aluminum-free high-temperature alloy.
[0016] Preferably, the composite deoxidizing sulfur agent C comprises an iron-lanthanum alloy and carbon.
[0017] Lanthanum can help with deep deoxidation and further reduce the content of harmful elements in the melt. At the same time, lanthanum can form a fine dispersed phase in the high-temperature alloy to improve the performance of the high-temperature alloy.
[0018] Preferably, the amount of the composite deoxidizing sulfur agent C is 0.02-0.03% of the total mass of the aluminum-free high-temperature alloy.
[0019] Preferably, the melt tempering treatment step includes: electromagnetic stirring at a speed of 300-400 Hz for 1-3 min every 3-5 min; the argon blowing step includes blowing argon to a pressure of 0.3-0.5 MPa; and the crucible is a zirconia crucible.
[0020] Melt tempering treatment helps the slag in the high-temperature alloy melt to float up, and improves the dynamic conditions through electromagnetic stirring treatment, which promotes the removal of harmful elements; argon blowing can help improve the dynamic conditions, promote the removal of slag, and enhance the effect of magnesium. At the same time, argon can promote the homogenization of the alloy, reduce gas dissolution, and ultimately achieve the effect of deep removal of harmful elements.
[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. By adding three composite deoxidizing sulfur agents, the contents of oxygen, nitrogen and sulfur in the high-temperature alloy melt are gradually reduced. The three composite deoxidizing sulfur agents work together through the principles of precipitation deoxidation and diffusion deoxidation to help remove oxygen in the high-temperature alloy through gas and slag. Nitrogen and sulfur simultaneously form nitrides and sulfides and are discharged from the system. The magnesium element in the nickel-magnesium alloy further helps the removal of harmful elements by forming oxides and sulfides, while improving the properties of the slag, promoting slag agglomeration and floating, and improving the purity of the high-temperature alloy. Through two refining, melt tempering treatment and high-temperature purification treatment, the oxygen, nitrogen and sulfur in the high-temperature alloy melt are removed, the content of harmful impurities is reduced, the segregation of alloy elements is reduced, and the performance of the high-temperature alloy is improved.
[0022] 2. Silicon-calcium cored wire can effectively penetrate into the molten steel, reduce the influence of rapid evaporation of calcium on the deoxidation and desulfurization performance, and improve the removal effect of harmful elements. At the same time, calcium helps to remove silicon oxides and sulfides, reducing the influence of inclusions on the performance of high-temperature alloys.
[0023] 3. Melt tempering treatment helps the slag in the high-temperature alloy melt to float up, and the electromagnetic stirring treatment improves the dynamic conditions and promotes the removal of harmful elements; argon blowing can help improve the dynamic conditions, promote the removal of slag, and enhance the effect of magnesium. At the same time, argon can promote the homogenization of the alloy, reduce gas dissolution, and ultimately achieve the effect of deep removal of harmful elements. DETAILED DESCRIPTION
[0024] The present application example discloses a method for smelting an aluminum-free high-temperature alloy. The raw materials used in the present application can be obtained from commercially available raw materials unless otherwise specified. The present application is further described in detail below in conjunction with the examples: Example 1 A method for smelting an aluminum-free high-temperature alloy, wherein the high-temperature alloy comprises the following components in percentage by mass: 35% nickel, 2.7% tantalum, 2.4% molybdenum, 10% cobalt, 12% chromium, 3.2% niobium, 1.2% titanium, 0.1% zirconium, and the remainder is iron and unavoidable impurities.
[0025] (1) placing a nickel plate at the bottom of a zirconia crucible, adding a composite deoxidizing sulfur agent A accounting for 0.5% of the total mass of the aluminum-free high-temperature alloy, and then sequentially placing nickel, molybdenum, tantalum, cobalt, chromium and iron at the bottom of the crucible, evacuating the crucible to a vacuum degree of ≤5Pa, supplying power to increase the power and starting melting, and after the materials are melted, heating to 1650°C, adding a composite deoxidizing sulfur agent B accounting for 0.05% of the total mass of the aluminum-free high-temperature alloy and refining for 40 minutes; the composite deoxidizing sulfur agent is a silicon-manganese alloy and carbon, the mass ratio of the silicon-manganese alloy to the carbon is 1:2, the silicon-manganese alloy has a silicon mass content of 50%, a manganese mass content of 25%, and the remainder is iron; the composite deoxidizing sulfur agent B is a silicon-calcium cored wire and carbon, the mass ratio of the silicon-calcium cored wire to the carbon is 1:1, the silicon-calcium cored wire includes a strip steel sheet and a core powder layer, the core powder layer includes 27% silicon, 17% cerium and 56% calcium, and the silicon-calcium cored wire is fed at a speed of 1.8 m / s; (2) After refining, the temperature is lowered until the alloy liquid surface solidifies, and niobium, titanium and zirconium are added in sequence. Electric heating is performed until the added materials are completely melted, and electromagnetic stirring is performed at a speed of 300 Hz for 1 minute every 3 minutes, and the melt is tempered for 30 minutes; (3) Adding a composite deoxidizing sulfur agent C accounting for 0.02% of the total mass of the aluminum-free high-temperature alloy to the tempered melt, the composite deoxidizing sulfur agent C is an iron-lanthanum alloy and carbon, the mass ratio of the iron-lanthanum alloy to the carbon is 1:1, the mass content of lanthanum in the iron-lanthanum alloy is 25%, and the mass content of iron is 75%. Maintaining the melt temperature at 1600° C., performing secondary refining for 15 minutes, after completing the secondary refining, cooling to the surface of the alloy liquid after film formation, adding a nickel-magnesium alloy until it is completely melted, the nickel-magnesium alloy having a nickel mass content of 70% and a magnesium content of 30%, heating to 1650° C., blowing argon gas from the bottom of the crucible to a gas pressure of 0.3 MPa, cooling to 1550° C. and maintaining the temperature for 30 minutes, completing the high-temperature purification treatment, performing live continuous casting, completing the alloy smelting, and obtaining an aluminum-free high-temperature alloy.
[0026] Example 2 A method for smelting an aluminum-free high-temperature alloy, wherein the high-temperature alloy comprises the following components in percentage by mass: 45% nickel, 2.3% tantalum, 1.6% molybdenum, 8% cobalt, 10% chromium, 2.5% niobium, 0.8% titanium, 0.05% zirconium, and the remainder is iron and unavoidable impurities.
[0027] (1) placing a nickel plate at the bottom of a zirconia crucible, adding a composite deoxidizing sulfur agent A accounting for 1% of the total mass of the aluminum-free high-temperature alloy, and then sequentially placing nickel, molybdenum, tantalum, cobalt, chromium and iron at the bottom of the crucible, evacuating the crucible to a vacuum degree of ≤5Pa, supplying power to increase the power and starting melting, and after the materials are melted, heating to 1650°C, adding a composite deoxidizing sulfur agent B accounting for 0.1% of the total mass of the aluminum-free high-temperature alloy and refining for 40 minutes; the composite deoxidizing sulfur agent is a silicon-manganese alloy and carbon, the mass ratio of the silicon-manganese alloy to the carbon is 1:2, the silicon-manganese alloy has a silicon mass content of 50%, a manganese mass content of 25%, and the remainder is iron; the composite deoxidizing sulfur agent B is a silicon-calcium cored wire and carbon, the silicon-calcium cored wire includes a strip steel sheet and a core powder layer, the core powder layer includes 31% silicon, 15% cerium and 54% calcium, and the silicon-calcium cored wire is fed at a speed of 1.8 m / s; (2) After refining, the temperature is lowered until the alloy liquid surface solidifies, and niobium, titanium and zirconium are added in sequence. Electric heating is performed until the added materials are completely melted, and electromagnetic stirring is performed at a speed of 400 Hz for 3 minutes every 5 minutes, and the melt is tempered for 30 minutes; (3) Adding a composite deoxidizing sulfur agent C accounting for 0.03% of the total mass of the aluminum-free high-temperature alloy to the tempered melt, the composite deoxidizing sulfur agent C is an iron-lanthanum alloy and carbon, the mass ratio of the iron-lanthanum alloy to the carbon is 1:1, the mass content of lanthanum in the iron-lanthanum alloy is 25%, and the mass content of iron is 75%. Maintaining the melt temperature at 1600° C., performing secondary refining for 15 minutes, after completing the secondary refining, cooling to the surface of the alloy liquid after film formation, adding a nickel-magnesium alloy until it is completely melted, the nickel-magnesium alloy having a nickel mass content of 70% and a magnesium content of 30%, heating to 1650° C., blowing argon gas from the bottom of the crucible to a gas pressure of 0.3 MPa, cooling to 1550° C. and maintaining the temperature for 30 minutes, completing the high-temperature purification treatment, performing live continuous casting, completing the alloy smelting, and obtaining an aluminum-free high-temperature alloy.
[0028] Example 3 A method for smelting an aluminum-free high-temperature alloy, wherein the high-temperature alloy comprises the following components in percentage by mass: 40% nickel, 2.5% tantalum, 2% molybdenum, 9% cobalt, 11% chromium, 2.85% niobium, 1% titanium, 0.075% zirconium, and the remainder is iron and unavoidable impurities.
[0029] (1) placing a nickel plate at the bottom of a zirconia crucible, adding a composite deoxidizing sulfur agent A accounting for 0.75% of the total mass of the aluminum-free high-temperature alloy, and then sequentially placing nickel, molybdenum, tantalum, cobalt, chromium and iron at the bottom of the crucible, evacuating the crucible to a vacuum degree of ≤5Pa, supplying power to increase the power and starting melting, and after the materials are melted, heating to 1650°C, adding a composite deoxidizing sulfur agent B accounting for 0.075% of the total mass of the aluminum-free high-temperature alloy and refining for 40 minutes; the composite deoxidizing sulfur agent is a silicon-manganese alloy and carbon, the mass ratio of the silicon-manganese alloy to the carbon is 1:2, the silicon-manganese alloy has a silicon mass content of 50%, a manganese mass content of 25%, and the balance is iron; the composite deoxidizing sulfur agent B is a silicon-calcium cored wire and carbon, the silicon-calcium cored wire includes a strip steel sheet and a core powder layer, the core powder layer includes 29% silicon, 16% cerium and 55% calcium, and the silicon-calcium cored wire is fed at a speed of 1.8 m / s; (2) After refining, the temperature is lowered until the alloy liquid surface solidifies, and niobium, titanium and zirconium are added in sequence. Electric heating is performed until the added materials are completely melted, and electromagnetic stirring is performed at a speed of 350 Hz for 2 minutes every 4 minutes, and the melt is tempered for 30 minutes; (3) Adding a composite deoxidizing sulfur agent C accounting for 0.025% of the total mass of the aluminum-free high-temperature alloy to the tempered melt, the composite deoxidizing sulfur agent C is an iron-lanthanum alloy and carbon, the mass ratio of the iron-lanthanum alloy to the carbon is 1:1, the mass content of lanthanum in the iron-lanthanum alloy is 25%, and the mass content of iron is 75%. Maintaining the melt temperature at 1600° C., performing secondary refining for 15 minutes, after completing the secondary refining, cooling to the surface of the alloy liquid after conjunctivae, adding a nickel-magnesium alloy until it is completely melted, the nickel-magnesium alloy having a nickel mass content of 70% and a magnesium content of 30%, heating to 1650° C., blowing argon gas from the bottom of the crucible to a gas pressure of 0.3 MPa, cooling to 1550° C. and maintaining the temperature for 30 minutes, completing the high-temperature purification treatment, performing live continuous casting, completing the alloy smelting, and obtaining an aluminum-free high-temperature alloy.
[0030] Example 4 Example 4 is based on Example 3. The only difference between Example 4 and Example 3 is that the amount of the composite deoxidizing sulfur agent A in Example 4 accounts for 0.3% of the total mass of the aluminum-free high-temperature alloy.
[0031] Example 5 Example 5 is based on Example 3. The only difference between Example 5 and Example 3 is that the amount of the composite deoxidizing sulfur agent A in Example 5 accounts for 1.5% of the total mass of the aluminum-free high-temperature alloy.
[0032] Example 6 Example 6 is based on Example 3. The only difference between Example 6 and Example 3 is that in Example 6, the composite deoxidizing sulfur agent A is replaced by carbon.
[0033] Example 7 Example 7 is based on Example 3. The only difference between Example 7 and Example 3 is that the amount of the composite deoxidizing sulfur agent B in Example 7 accounts for 0.02% of the total mass of the aluminum-free high-temperature alloy.
[0034] Example 8 Example 8 is based on Example 3. The only difference between Example 8 and Example 3 is that the amount of the composite deoxidizing sulfur agent B in Example 8 accounts for 0.15% of the total mass of the aluminum-free high-temperature alloy.
[0035] Example 9 Example 9 is based on Example 3. The only difference between Example 9 and Example 3 is that in Example 9, the composite deoxidizing sulfur agent B is replaced by silicon-calcium alloy and carbon, and the mass ratio of silicon-calcium alloy to carbon is 1:1.
[0036] Example 10 Example 10 is based on Example 3. The only difference between Example 10 and Example 3 is that the amount of the composite deoxidizing sulfur agent C in Example 10 accounts for 0.01% of the total mass of the aluminum-free high-temperature alloy.
[0037] Embodiment 11 Example 11 is based on Example 3. The only difference between Example 11 and Example 3 is that the amount of the composite deoxidizing sulfur agent C in Example 11 accounts for 0.05% of the total mass of the aluminum-free high-temperature alloy.
[0038] Example 12 Example 12 is based on Example 3. The only difference between Example 12 and Example 3 is that in Example 12, the composite deoxidizing sulfur agent C is replaced by carbon.
[0039] Performance testing (1) Select "ASTM E 1019-08" as the standard to detect the content of oxygen, nitrogen and sulfur elements in high-temperature alloys. Prepare three specimens for each sample, take the average value after measurement, and record the results in Table 1.
[0040] (2) Determination of scum content: Measure and record the scum content in each example in Table 1.
[0041] Table 1 Test results of impurity element content and slag content of aluminum-free high-temperature alloy As shown in Table 1, the oxygen content of Examples 1-3 is less than 2.7 ppm, the nitrogen content is less than 2.6 ppm, the sulfur content is less than 1.3 ppm, and the dross content is less than 0.6%, which shows that the high-temperature alloy prepared in this application has good purity.
[0042] As can be seen from Table 1, the only difference between Examples 4, 5, and 6 and Example 3 is that in Example 4, the amount of the composite deoxidizing sulfur agent A is 0.3% of the total mass of the aluminum-free high-temperature alloy, and in Example 5, the amount of the composite deoxidizing sulfur agent A is 1.5% of the total mass of the aluminum-free high-temperature alloy. In Example 6, the composite deoxidizing sulfur agent A is replaced with carbon. Compared with Example 3, the purity of the high-temperature alloy in Examples 4, 5, and 6 is reduced. This is because the amount and composition of the composite deoxidizing sulfur agent A are changed. Too much or too little composite deoxidizing sulfur agent A will affect the removal effect of oxygen, nitrogen, and sulfur elements, increase the content of inclusions in the melt, and thus affect the purity of the alloy.
[0043] As can be seen from Table 1, the only difference between Examples 7, 8, and 9 and Example 3 is that the amount of the composite deoxidizing sulfur agent B in Example 7 accounts for 0.02% of the total mass of the aluminum-free high-temperature alloy, the amount of the composite deoxidizing sulfur agent B in Example 8 accounts for 0.15% of the total mass of the aluminum-free high-temperature alloy, and the composite deoxidizing sulfur agent B is replaced with silicon-calcium alloy and carbon in Example 9, and the mass ratio of silicon-calcium alloy to carbon is 1:1. Compared with Example 3, the purity of the high-temperature alloy in Examples 7, 8, and 9 is reduced. This is because the amount and composition of the composite deoxidizing sulfur agent are adjusted. After adjusting the amount, it will affect the interaction between the various composite deoxidizing sulfur agents and affect the overall deoxidation and desulfurization effect; replacing the silicon-calcium cored wire with a silicon-calcium alloy will affect the delivery depth of the silicon-calcium alloy, affect the removal of harmful elements, and thus affect the purity of the alloy.
[0044] As can be seen from Table 1, the only difference between Examples 10, 11, and 12 and Example 3 is that in Example 10, the amount of the composite deoxidizing sulfur agent C accounts for 0.01% of the total mass of the aluminum-free high-temperature alloy, and in Example 11, the amount of the composite deoxidizing sulfur agent C accounts for 0.05% of the total mass of the aluminum-free high-temperature alloy. In Example 12, the composite deoxidizing sulfur agent C is replaced by carbon. Compared with Example 3, the purity of the high-temperature alloy in Examples 10, 11, and 12 is reduced. This is because changing the amount of the composite deoxidizing sulfur agent will affect the removal effect of harmful elements; when the composite deoxidizing sulfur agent C is replaced by carbon, the deoxidation and desulfurization effect and doping of lanthanum are lacking, and the harmful elements in the melt lack deep removal, so the purity of the high-temperature alloy is reduced.
[0045] This specific embodiment is only an explanation of the present application, and it is not a limitation of the present application. Through the above description, relevant staff can make various changes and modifications without deviating from the technical idea of the present application. The technical scope of the present application is not limited to the content in the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for smelting an aluminum-free high-temperature alloy, characterized in that: The following steps are involved: (1) placing a nickel plate at the bottom of a crucible, adding a composite deoxidizing sulfur agent A, and then placing nickel, molybdenum, tantalum, cobalt, chromium and iron at the bottom of the crucible in order, vacuuming and melting the materials, raising the temperature after the materials are melted, and adding a composite deoxidizing sulfur agent B for refining; (2) After refining, the temperature is lowered until the alloy liquid surface solidifies, and niobium, titanium and zirconium are added in sequence. Electric heating is applied until the added materials are completely melted, and then the melt is stirred for tempering treatment; (3) Adding composite deoxidizing sulfur agent C to the tempered melt for secondary refining, cooling the alloy liquid to form a film on the surface, adding nickel-magnesium alloy until it is completely melted, heating the alloy liquid, blowing argon gas from the bottom of the crucible, cooling the alloy liquid and then keeping the temperature, completing the high-temperature purification treatment, and performing continuous casting with electricity to complete the alloy smelting to obtain an aluminum-free high-temperature alloy.
2. The smelting method of an aluminum-free high-temperature alloy according to claim 1, characterized in that: The aluminum-free high-temperature alloy includes the following components in mass fractions: 35-45% nickel, 2.3-2.7% tantalum, 1.6-2.4% molybdenum, 8-10% cobalt, 10-12% chromium, 2.5-3.2% niobium, 0.8-1.2% titanium, 0.05-0.1% zirconium, and the balance is iron and unavoidable impurities.
3. The smelting method of an aluminum-free high-temperature alloy according to claim 1, characterized in that: The composite deoxidizing sulfur agent A comprises silicon-manganese alloy and carbon.
4. The smelting method of an aluminum-free high-temperature alloy according to claim 3, characterized in that: The amount of the composite deoxidizing sulfur agent A is 0.5-1% of the total mass of the aluminum-free high-temperature alloy.
5. The method for smelting an aluminum-free high-temperature alloy according to claim 1, characterized in that: The composite deoxidizing sulfur agent B comprises a calcium-silicon cored wire and carbon, and the calcium-silicon cored wire comprises a steel sheet and a core powder layer.
6. The method for smelting an aluminum-free high-temperature alloy according to claim 5, characterized in that: The core powder layer includes 27-31% silicon, 15-17% cerium, and the balance is calcium.
7. The method for smelting an aluminum-free high-temperature alloy according to claim 6, characterized in that: The amount of the composite deoxidizing sulfur agent B is 0.05-0.1% of the total mass of the aluminum-free high-temperature alloy.
8. The method for smelting an aluminum-free high-temperature alloy according to claim 1, characterized in that: The composite deoxidizing sulfur agent C comprises an iron-lanthanum alloy and carbon.
9. The method for smelting an aluminum-free high-temperature alloy according to claim 8, characterized in that: The amount of the composite deoxidizing sulfur agent C is 0.02-0.03% of the total mass of the aluminum-free high-temperature alloy.
10. The method for smelting an aluminum-free high-temperature alloy according to claim 1, characterized in that: The melt tempering treatment step includes: electromagnetic stirring at a speed of 300-400 Hz for 1-3 minutes every 3-5 minutes; the argon blowing step includes blowing argon until the pressure is 0.3-0.5 MPa; and the crucible is a zirconia crucible.